Les adieux, l'absence et le retour : Sonate caracteristique pour le pianoforte compose?e par L van Beethoven ; me?tronomise?e par J. Moscheles. Oeuv. 81 - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Moscheles, Ignaz, 1794-1870 (editor):::Contributor:::::::::::: (Hamburg; A. Cranz; Germany, 2022)
Early edition of the Piano Sonata no. 26 in E-flat major, op. 81a, published by A. Cranz in Hamburg, with metronome markings added by Iganz Moscheles.